Pengaruh Tingkat Pengetahuan Pajak dan Penerapan E-Billing Terhadap Kepatuhan Wajib Pajak Orang Pribadi dan Badan di Kantor Pelayanan Pajak Pratama Pare - Mutiara Rosyidah (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This research is to know: (1) the effect of tax knowledge on taxpayer compliance of individual and corporate. (2) the effect of the application of E-Billing on taxpayer compliance of individuals and corporate. (3) the effect of tax knowledge and the application of E-Billing on taxpayer compliance of individuals and corporate. Population in this research is individual taxpayer and taxable income corporate (PKP) at Tax Office Pratama Pare. Sampling technique is by random sampling with a sample size of 110 respondents. This study uses primary data that is questionnaire. This research uses quantitative descriptive method with multiple regression analysis model. The results of this study indicate that: (1) The level of tax knowledge has a positive and significant impact on taxpayer compliance of individuals and corporate. (2) The application of E-Billing has a positive and significant impact on taxpayer compliance of individuals and corporate.(3) The level of tax knowledge and application of E-Billing has a positive and significant effect on taxpayer compliance of individuals and corporate.